Analysis of 4-Level Web-Based Instruments on Dynamic Electricity Material Using the Rasch Model for High School Learners - Moh Dimas Feri Hermansyah; Ernasari Ernasari; Maryani Maryani (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2025)
Web-based 4-tier instrument analysis on dynamic electricity material is one of the diagnostic tests that can determine the extent of understanding of the concepts that students have according to the level of confidence of the answers and the reasons they answer. The purpose of this study was to determine the feasibility of the instrument using Rasch Model analysis. Rasch Model analysis is assisted by Winstep software to analyze the scores generated from test instruments with the aim of knowing MNSQ Outfit, ZSTD Outfit, Item Measure, Item fit order, Item reliability, and Alpha Cornbach. This research is a descriptive type with quantitative descriptive research methods. The sample of this study was taken from the population derived from class XII students with a total of 91 people who have learned the concept of dynamic electricity in Jember city with purposive sampling technique. The instrument used was a web-based Four-tier diagnostic test consisting of 30 questions. The Rasch Model analysis results stated that the person reliability values of 0.76 and 0.78 were in the sufficient category, the item reliability values of 0.93 and 0.94 were in the excellent category, and the Cronbach Alpha Alpha (reliability) value of 0.78 was in the good category, indicating that the interaction between respondents and items was in the good category. This shows that the diagnostic test instrument is feasible, valid, and reliable.